AGRA BAZAR AS A CULTURAL ARCHIVE: TRADITION, IDENTITY, AND THE PEOPLE’S THEATRE - Kaur, Paramjit (International Journal of Research -GRANTHAALAYAH, 2018)
This paper examines Agra Bazar (1954), Habib Tanvir’s seminal play, as a cultural archive that preserves and performs Indian traditions through people’s theatre. Set against the backdrop of post-independence India, the play utilizes folk performance, vernacular language, and indigenous storytelling techniques to challenge elite and colonial aesthetics. Central to the narrative is the poetry of Nazir Akbarabadi, whose celebration of everyday life and common people becomes a vehicle for cultural resistance and identity formation. The study employs performance theory, particularly Diana Taylor’s concept of the repertoire, to argue that Agra Bazar functions as a living, embodied archive. Through textual analysis and critical scholarship, the paper highlights how Tanvir’s theatre reclaims marginalized voices and promotes a pluralistic vision of Indian identity. Agra Bazar is thus seen as both a historical document and a dynamic site of cultural memory, reinforcing the role of theatre in shaping collective consciousness.